2021
DOI: 10.1088/1755-1315/782/4/042056
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics of Mangosteen plants (Garcinia mangostana L.) in Langkat District, North Sumatera, Indonesia

Abstract: Mangosteen is one of Indonesia’s native fruit plants that has very large export potential, but at this time the age of mangosteen plants in smallholder plantations has reached more than ten years, so fulfilment of mangosteen export needs will be hindered. This study was aimed to identify the morphological characteristics of mangosteen plants and as a conservation material in several sub-districts (Wampu, Stabat and Tanjung Pura) in Langkat district of North Sumatra, Indonesia, with an accidental sampling surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The use of Garcinia mangostana L., commonly known as mangosteen, in synthesizing ZnO-CuO NCs has not been explored. Mangosteen is a seasonal fruit in the Clusiacae family and is commonly found in tropical countries [25][26][27][28][29]. It contains numerous phytochemicals, such as xanthones, flavonoids and terpene [30][31][32][33], which have the potential to form stable colloidal nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Garcinia mangostana L., commonly known as mangosteen, in synthesizing ZnO-CuO NCs has not been explored. Mangosteen is a seasonal fruit in the Clusiacae family and is commonly found in tropical countries [25][26][27][28][29]. It contains numerous phytochemicals, such as xanthones, flavonoids and terpene [30][31][32][33], which have the potential to form stable colloidal nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…According to several epidemiological studies, mangosteen pericarp is often used as an active ingredient in traditional medicines in South East Asia for chronic diseases that involve chronic inflammation . Mangosteen (Garcinia mangostana L.) is one of commonly grown fruit trees in South East Asia countries, such as Thailand, Indonesia, and Malaysia Failla & Gutiérrez-Orozco, 2017;Syahputra et al, 2021). It is reported that the pericarp of mangosteen fruit contains numerous phytochemicals with various health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…G. mangostana L., commonly called mangosteen, is an endemic evergreen tree species which is native to tropical countries such as Thailand, Indonesia and Malaysia. It belongs to the Clusiacae family [ 47 , 48 ], and mangosteen has been described as the “fruit queen” due to its incomparable flavor and aroma [ 49 , 50 , 51 ]. The mangosteen contains large amounts of phenolics and antioxidants [ 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%